OPTIMALISASI KETERAMPILAN GURU UNTUK MENGHASILKAN SISWA BERKEBUTUHAN KHUSUS YANG TERAMPIL DAN MANDIRI DI SEKOLAH LUAR BIASA NEGERI MEULABOH - Dian Kristanti; Cut Eva Nasryah; Agus Kistian (LPPM Universitas Cipta Mandiri, 2024)
This service activity aims to: 1) Optimize the skills of teachers at the Meulaboh State Special School so that they can produce students with special needs who are skilled and independent; 2) Increase the interest of students with special needs in learning mathematics; 3) Helping students with special needs in learning, especially in terms of supporting facilities such as tools and materials needed during activities at school. The subjects in this service consisted of 25 teachers and 11 students with special needs at the SMPLB and SMALB levels at the Meulaboh State SLB. The methods used in this service activity are observation, questionnaires, workshops, training, and data analysis of students' skills and interests. The outputs produced in this service activity include: 1) producing 80% of teachers who have vocational skills at SLBN Meulaboh; 2) produce 60% of students with special needs who are skilled and independent; 3) produce 70% of students with special needs who are interested in studying mathematics; 4) publication in the national journal Genta Mulia; 4) publication in West Aceh electronic mass media; 5) activity videos uploaded to social media, STKIP Bina Bangsa Meulaboh YouTube and Meulaboh State SLB YouTube.